Reliability and validity of self-report questions for assessing levels of physical activity and sedentary time in adult childhood cancer survivors - Laura Jess; Marianne Jarfelt; Maria Bäck (BMC, 2024)
Abstract Background Regular physical activity and limited sedentary time are recommended for adult childhood cancer survivors. The Swedish National Board of Health and Welfare designed a questionnaire to assess levels of physical activity (BHW-Q), including two questions: one on vigorous physical activity (BHW-Q VPA) and one on moderate physical activity (BHW-Q MPA). Furthermore, a single-item question was developed to measure sedentary time (SED-GIH-Q). These questions are recommended for clinical practice and have been found valid for the general population but have so far not been tested in adult childhood cancer survivors. The aim of the study was to assess test-retest reliability, agreement and criterion-related validity of the BHW-Q and the SED-GIH-Q in adult childhood cancer survivors. Method A non-experimental methodological study. In total 60 participants (50% women), median age 28 (min-max 18-54) years were included at the Long-Term Follow-Up Clinic at Sahlgrenska University Hospital. Participants were instructed to wear an accelerometer for seven days, and to answer the BHW-Q and the SED-GIH-Q before and after the seven days. Test-retest reliability and criterion-related validity comparing the BHW-Q and SED GIH-Q with accelerometer data were calculated with weighted Kappa (k) (agreement) and by using Spearman´s rho (r) (correlation). Results Test-retest reliability regarding the SED-GIH-Q showed a high agreement (k = 0.88) and very strong correlation (r = 0.93), while the BHW-Q showed a moderate agreement and moderately strong correlation, BHW-Q VPA (k = 0.50, r = 0.64), BHW-Q MPA (k = 0.47, r = 0.58). Both the agreement and the correlation of the criterion-related validity were interpreted as fair for the BHW-Q VPA (k = 0.29, r = 0.45), while the agreement for BHW-Q MPA was interpreted as low (k = 0.07), but the correlation as fair (r = 0.37). The agreement of the SED-GIH-Q (k = 0.13) was interpreted as low and the correlation as poor (r = 0.26). Conclusion These simple questions assessing physical activity and sedentary time can be used as screening tools in clinical practice to identify adult childhood cancer survivors in need of support to increase physical activity level. Further development is needed on the design of a sufficiently valid question measuring sedentary time. Trial registration This research project was registered in the Swedish National Database of Research and Development; identifier 275251, November 25, 2020. https://www.researchweb.org/is/vgr/project/275251 .